Modernization of electrical equipment as a way of reducing the risks of emergency situations at nuclear power plants - Levchenko, Larysa O.; Radionov, Oleksandr V. (Kyiv National University of Construction and Architecture, 2023)
An analysis of major accidents in the electric power and coal industry was carried out. It is shown that for many types of technological equipment, the cause of failure was the unsatisfactory performance of the seals. It is shown that in two known nuclear accidents, the cause is the failure of coolant supply systems. Moreover, it had catastrophic consequences at the Fukushima nuclear power plant. The direct cause of the cessation of cooling of the reactors was the ingress of water into the electric motors of the circulation pumps. Most electric drives of nuclear power plants are synchronous electric motors. Turbogenerators are also synchronous four-pole electric machines of great value, which determines the expediency of increasing their reliability and service life. The solution to this problem is possible with the help of magnetic fluid sealing complexes (MFCs). To compare the level of man-made safety when using MFCs and traditional sealing systems, an improved method of risk assessment is proposed, developed at the expense of a systematic analysis of sealing complexes of equipment of hazardous industries for synchronous electric motors of the SDN type under different modes of operation, power and revolutions of the rotating shaft. The man-made risk assessment shows that the level of man-made danger is reduced by 1.5 to 4 times when sealants are introduced.